An Analysis of Village Governance With Organizational Commitment as a Moderating Variable - Oktari, Vera; Afifah, Ulfa (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
The number of administrative violations and corruption cases at the village level has been in the spotlight recently. Good village governance is one of the steps to overcome it. This study aims to identify the factors that influence village governance and examine the moderating effect of organizational commitment on the relationships between village financial management and apparatus competence in village governance. This study was conducted in the Village Government in Rokan Hilir Regency and employed quantitative data analysis. The data was obtained using a questionnaire, and the respondents were selected using purposive sampling. This study used an analysis method using the structural equation model (SEM). The result shows that the government's internal control system and village financial management can affect village governance in Rokan Hilir Regency. However, apparatus competence cannot influence village governance, and organizational commitment cannot strengthen the performance of the apparatus in implementing village governance. Nevertheless, organizational commitment is needed to enhance the relationship between village financial management and governance in Rokan Hilir.